Study the Optical and Spectral Properties of the Acridine Dye As an Effective Medium in Dye Lasers (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this study, the absorption and fluorescence spectra of the dissolved Acridine solution were studied in ethanol and different concentrations. The optical properties (absorption coefficient, linear refraction) and spectral characteristics (Fluorescence time and quantitative fluoridation efficiency) were calculated. It is observed that increasing the concentration increases the absorbance values and decreases the permeability values, thus increasing the values of the absorption coefficient and the refractive index. Also, the values of the fluorine intensity increase. The peak of the emission spectrum is transferred to the longer wavelengths.